Mapping and Examining the Subcontracting Process Adopted by Iraqi Quasi-Governmental Construction Companies - S. A. Al-Obaidi, Taha; Higham, Anthony (International Journal of Engineering and Technology, 2018)
In todayâ€™s dynamic business environment, a process view has become a mandatory requirement for any organization striving to excel and stay ahead of the competition. By focusing on improving operational processes, organizations can enhance their overall performance and establish a robust competitive advantage through cost and time reduction alongside increasing the quality of products. With a view of improving the performance of Iraqi Quasi-Governmental Construction Companies (IQGCCs) through instituting the process view. This research, particularly, was designed to map examine the subcontracting process currently in use by IQGCCs. To achieve this aim, three of IQGCCs were selected as case studies to collect the required data. Semi-structured interviews with experts from different management levels of these companies supported by document review and focus groups were the key techniques employed to gather and validate the field data. Four factors, namely: government restrictions, authority distributions, management system and communication system, were identified as the key underpinning causes of the current challenges and barriers to efficiency in the subcontracting process. Accordingly, more studies to improve the efficiency of the current subcontracting process are extremely required.Â